Oxytocin and chronic pain in humans (2019)
Oxytocin (OT) is a long known neuropeptide, and it's uses in clinical practice, mainly those regarding obstetrics have been thoroughly studied. However, there's been an increasing interest in identifying other roles OT plays in emotion, cognition, perception and higher cognitive processing. OT is also believed o have a mayor role in the physiology and physiopathol-ogy of pain. We have reviewed existent literature and current human studies on the relationship between OT and chronic pain. The present work compiles a significant number of research papers and may cast some light on a remarkably interesting and promising matter. © 2019 Ediciones Doyma, S.L. All rights reserved.